'Disenchanted with the state': confronting the limits of neoliberal multiculturalism in Colombia. Issue 4 (1st October 2020) - Dest, Anthony
ABSTRACT: The Colombian government's embrace of multicultural policies in the 1990 s had far-reaching implications for black and indigenous struggles for self-determination and autonomy. In the context of widespread violence, multicultural policies seemed to offer a semblance of protection. However, after nearly three decades of multicultural reforms, black and indigenous communities continue to face disproportionate violence and dispossession at the hands of the state, multinational corporations, drug traffickers, and other armed groups. This article explores the autonomy/inclusion dialectic in order to understand why some black and indigenous social movements are turning away from the state's recognition policies.